Antimicrobial Sensitivity Pattern of Causative Agents of Urinary Tract Infection in Children Between 1 to 15 Years - Sah, Vijay Kumar; Yadav, Sunil Kumar; Giri, Arun; Singh, Sandip Kumar (Journal of College of Medical Sciences-Nepal, 2023)
Background: The presence of actively multiplying organisms in the urinary tract implies urinary tract infection. Although it is infrequently associated with mortality, it is still an important cause of morbidity in the pediatric age group. Prompt diagnosis and early initiation of appropriate antibiotics in children reduce the morbidities associated with urinary tract infection. The objective of the study was to find out the causative agents of urinary tract infections and their antibiotic sensitivity pattern in pediatric patients. Methods: This was a cross-sectional study conducted in the department of pediatrics over a period of 12 months and 80 patients fulfilled the inclusion criteria. The modes of presentation, laboratory investigation reports which included urine routine microscopy, bacterial isolates with colony count from the urine culture, and antibiotic sensitivity pattern were documented. Descriptive statistics were used for analysis of data. Result: Escherichia coli was the most common organism isolated (55.9%). Most of them were sensitive to amikacin.The highest degree of resistance was noticed with ampicillin. Conclusion: Aminoglycosides like amikacin can be considered as first-line drugs in urinary tract infection. Keywords: antibiotics, children, urinary tract infections.